(untitled) - Vieira, Robert (Indianapolis, I.N., 2003)
SQL Server 2000 is the latest and most powerful version of Microsoft's data warehousing and relational database management system. This new release is tightly integrated with Windows 2000 and offers more support for XML, as well as improved Analysis Services for OLAP and data mining. Professional SQL Server 2000 provides a comprehensive guide to programming with SQL Server 2000, from a complete tutorial on Transact-SQL to an in-depth discussion of new features, such as indexed views, user-defined functions, and the wealth of new SQL Server features to support XML. Whether you're coming to SQL Server 2000 from another relational database management system, upgrading your existing system, or perhaps wanting to add programming skills to your DBA knowledge, you'll find what you need in this book to get to grips with SQL Server 2000 development.
Keywords: Máy chủ SQL,SQL server